Analysis of Contribution Assistance Recipients' Utilization of National Health Insurance Participants - Dwi Noerjoedianto; Adila Solida; Arnild Augina Mekarisce (Journal of Applied Nursing and Health, 2022)
Background: Contribution Assistance coverage for National Health Insurance Participants Participation among recipients is greater than that of non-participants, but the use of health services by National Health Insurance PBI participants in Indonesia remains relatively low. This study aims to determine in 2021 which factors influence the utilization of health services by National Health Insurance PBI group participants in Jambi City. Methods: This study is a quantitative cross-sectional investigation. The sample consisted of 106 random samples collected using the technique of accidental sampling. In this study, the independent variables were education, occupation, knowledge, attitudes, perceptions of health conditions, affordability, and information, while the dependent variable was health service utilization. Respondents filled out questionnaires to generate data. The data analysis consisted of univariate and bivariate (chi-square) tests. Result: This study's findings indicate that the majority of respondents, 61.3%, do not utilize health services. Knowledge (0.000), attitudes (0.003), perception of health conditions (0.012), and information are associated with the utilization of health services, according to this study's statistical analyses (0.000). In addition, there is no correlation between education (0.147), occupation (0.295), affordability (0.787), and the utilization of health services among National Health Insurance (JKN) PBI group participants. Conclusion: There is a correlation between knowledge, attitudes, perceptions of health conditions, and information and the utilization of health services by National Health Insurance for the PBI Group participants in Jambi City.